Quand l’ordre scolaire s’ajuste à la rue : éduquer des jeunes déscolarisés dans un centre associatif à Tripoli (Liban) - Simone Spera (Revue des Mondes Musulmans et de la Méditerranée)
At a time when NGOs are taking charge of the education of young people who have remained excluded from the school system, ethnography can illustrate the diversity and the tensions in the pedagogical practices used to adapt the school order to a public of dropouts. Based on a study carried out in the centre of the NGO “Mouvement Social” in Tripoli (Lebanon), this article will show how two educators try to apply, in their own way, a pedagogy of autonomy and self-expression, while juggling the constraints of a context of social fragmentation and collapse. Such an educational style can coexist with so-called traditional pedagogical techniques. In order to establish closeness with the learners and foster their autonomy, it can also lead to reappropriating tropes in a playful manner, such as cunning in defiance of teacher authority.